REFLECTION OF THE NATIONAL MENTALITY IN THE LANGUAGE (Scientific journal of the Fergana State University, 2024)
This article describes the national mentality, which expresses the way of thinking of our people, and aspects of its manifestation in language. Language occupies an important place in the structure of mentality, as a form of expression of human thinking and a form of life; it is considered as a condition for knowing reality. At the same time, it is also a means of recording, storing and transmitting accumulated knowledge and experience from generation to generation.